Physical processes in the negative ion source with reflected discharge - Goretskii, V.P.; Ryabtsev, A.V.; Soloshenko, I.A.; Tarasenko, A.F.; Tschedrin, A.I. (Вопросы атомной науки и техники, 1999)
In this article the results of experimental and theoretical investigations of the physical processes in the negative ion source with reflected discharge are represented. This source was developed at the Institute of Physics of NAS of Ukraine. It is naturally, that for optimal utilization of the source one should know the mechanisms of formation and destruction of negative ions, mechanisms of small admixture influence on emission characteristics of the source and space-time evaluation of source plasma in the direction of extracted slit. All these problems were studied in the present work in detail.